Whose stories? Whose place? : place politics and the politics of place stories in Tromsø's Olympic debate - Kielland, Ingrid Marie (Universitetet i Tromsø, 2013)
Abstract The dissertation explores the relevance and potential of approaching place politics through personal and collective stories about place. It is based on a case study of a local debate over a controversial project to bid for the 2018 Winter Olympic Games in Tromsø, Northern Norway. The dissertation contributes to developing Doreen Massey´s work on the politics of a relational sense of place by looking at how interests and identities, propinquities and connectivities are negotiated and co-constructed through discursive practices. Four arguments are drawn from the case study: Place stories are mobile, and enable knowledge and experiences to travel across space and time. Place stories are also versatile, and can be used in different ways to do different kinds of discursive work. The political relevance of place stories is based on their function as discursive resources for political action. Approaching place politics through place stories is particularly useful because place stories combine interests, identities, propinquities and connectivities. The dissertation states that ambivalent stories about exclusion and inclusion, relevance and irrelevance, the near and the far away, contribute to producing power and to producing place. It emphasises the important role of personal stories about identities and belonging in negotiating place politics, and concludes that politics of identities should to a greater extent be included in academic and political discussions of interests, development and economics. Sammendrag Avhandlingen drøfter relevansen av og potensialet i stedsfortellinger som en empirisk og analytisk tilnærming til stedspolitikk. Utgangspunktet for avhandlingen er en casestudie av den lokale debatten i Tromsø knyttet til søknaden om å arrangere vinter-OL i 2018. Avhandlingen bidrar til å videreutvikle Doreen Masseys relasjonelle og politiske stedsperspektiver ved å utforske hvordan interesser og identiter, nærhet og forbindelser forhandles og konstrueres gjensidig gjennom diskursive praksiser. På ...